2013
DOI: 10.1088/0004-6256/146/2/37
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Resolved Infrared Spectroscopy and Photometry of V1500 Cygni, and a Search for Similar Old Classical Novae

Abstract: We present phase-resolved near-infrared photometry and spectroscopy of the classical nova V1500 Cyg to explore whether cyclotron emission is present in this system. While the spectroscopy do not indicate the presence of discrete cyclotron harmonic emission, the light curves suggest that a sizable fraction of its near-infrared fluxes are due to this component. The light curves of V1500 Cyg appear to remain dominated by emission from the heated face of the secondary star in this system. We have used infrared spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…To get to the MMRD, the peak would have to be 2.5 mag brighter than observed, and this is not plausible. The extinction value from Harrison, Campbell, & Lyke (2013) is reliable, and A V is certainly not 2.5 mag larger. Further, Liu & Hu (2000) has confidently identified the quiescent counterpart, and it is certainly the source listed in the Gaia catalog.…”
Section: Possible Data Errors For the Mmrd Outliersmentioning
confidence: 87%
“…To get to the MMRD, the peak would have to be 2.5 mag brighter than observed, and this is not plausible. The extinction value from Harrison, Campbell, & Lyke (2013) is reliable, and A V is certainly not 2.5 mag larger. Further, Liu & Hu (2000) has confidently identified the quiescent counterpart, and it is certainly the source listed in the Gaia catalog.…”
Section: Possible Data Errors For the Mmrd Outliersmentioning
confidence: 87%
“…It would also be interesting to obtain new phase-resolved near-IR spectroscopy to search for emission from the cyclotron fundamentals. We re-examined the JHK spectra presented in Harrison et al (2013, obtained with NIRC on Keck in 2006), but could not find any evidence to support the presence of discrete cyclotron harmonic features in those data.…”
Section: Discussionmentioning
confidence: 93%
“…The highly variable 12 μm light curve of Z Cam during an outburst suggests that, like SS Cyg, it is a synchrotron source when near visual maximum. If so, it would join the small family of synchrotron emitting CVs: SS Cyg, AE Aqr, V1223 Sgr (Harrison et al 2010), and probably EX Hya (Harrison et al 2010) and GK Per (Harrison et al 2013). There is a significant number of non-magnetic CVs in the AllWISE survey catalog that have extreme (W2 − W3) colors that suggest that they too are sources of non-thermal emission.…”
Section: Discussionmentioning
confidence: 99%
“…Harrison & Gehrz (1992) originally reported a weak IRAS 12 μm detection of Z Cam (S ν = 0.09 ± 0.03 Jy). A reexamination of the IRAS detections for classical novae using WISE imaging data (Harrison et al 2013) showed that the majority of those detections were due to source confusion. This explanation cannot be used to dismiss the detection of Z Cam, as no WISE sources this bright exist within the IRAS detection radius for this source.…”
Section: The Mid-infrared Observations Of Z Cammentioning
confidence: 99%